Bromo Radical‐Mediated Photoredox Aldehyde Decarbonylation towards Transition‐Metal‐Free Hydroalkylation of Acrylamides at Room Temperature. Issue 2 (29th November 2021) - Sun, Zhaozhao; Huang, Huawen; Wang, Qiaolin; Deng, Guo‐Jun
Abstract: Herein, we report a visible‐light‐mediated hydroalkylation reaction of alkenes using easily available aldehydes as alkyl sources via bromo radical‐promoted photoredox decarbonylation. This protocol provides an alternative entry to C( sp 3 )−C( sp 3 ) bond formation and features considerable advantages including mild and clean reaction conditions, obviation for transition‐metal catalyst, and good functional group compatibility. Abstract :